2020
DOI: 10.1111/jth.14768
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal coagulation parameters are associated with poor prognosis in patients with novel coronavirus pneumonia

Abstract: Background In the recent outbreak of novel coronavirus infection in Wuhan, China, significantly abnormal coagulation parameters in severe novel coronavirus pneumonia (NCP) cases were a concern. Objectives To describe the coagulation feature of patients with NCP. Methods Conventional coagulation results and outcomes of 183 consecutive patients with confirmed NCP in Tongji hospital were retrospectively analyzed. Results The overall mortality was 11.5%, the non‐survivors revealed significantly higher D‐dimer and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

270
6,119
45
496

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 5,346 publications
(6,930 citation statements)
references
References 10 publications
270
6,119
45
496
Order By: Relevance
“…In our study, AT values in COVID-19 patients were found to be lower, whereas those of D-dimer, FDP, and FIB were found to be higher than in a control healthy population, thus confirming earlier similar findings [18]. This evidence would imply that routine hemostasis tests may be additional useful tools for improving early diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, AT values in COVID-19 patients were found to be lower, whereas those of D-dimer, FDP, and FIB were found to be higher than in a control healthy population, thus confirming earlier similar findings [18]. This evidence would imply that routine hemostasis tests may be additional useful tools for improving early diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…According to the severity and the evolution of the disease, n = 39 patients (52%) admitted to IW were moved after few days in ICU, while n = 6 (8%) died. In the population studied, the results of some relevant routine laboratory tests that may provide prognostic information, as suggested by other studies [8][9][10] showed (Table 1): lymphocytopenia (lymphocytes < 83% and 18% of patients respectively, increased D-Dimer (> 500 μg/L) and CRP concentrations (> 10 mg/L) in 31% and 85% of patients respectively, while PCT values higher than 0.5 μg/L were observed in 24% only. The time of hospitalization ranged between 9 and 60 days (median 17 days), but the comparison between biomarkers has been carried out considering only the results available at the same day.…”
Section: To the Editormentioning
confidence: 78%
“…In patients with clinical worsening not explained by an extension of lung opacities on CT, pulmonary embolism should be suspected and a contrast-enhanced CT examination should be performed if possible, taking into consideration the clinical severity and the renal function. Of note, patients with severe COVID-19 pneumonia have a marked elevation of d-dimers, so that this ddimer levels do no help identify those who have superimposed pulmonary embolism [16].…”
Section: Evolution During Follow-upmentioning
confidence: 99%